Risk factors and outcomes, a case series of ischemic stroke in children - Shirley L. Anggriawan; lrawan Mangunatmadja; Djajadiman Gatot; Sofyan lsmael; Najib Advani (Indonesian Pediatric Society Publishing House, 2009)
Ischemic strokes in children, although generally rare events, are more prevalent  than  commonly believed. Ischemic stroke in children have  been associated with coagulation disorders, cardiac anomalies, infections  and  trauma.